Levocetirizine orodispersible tablet by direct compression method - Gopal Satishkumar Gandhi, Dharmendra R. Mundhada , Shyamala Bhaskaran (Journal of Applied Pharmaceutical Science)
Orodispersible tablets are those that dissolve or disintegrate quickly in the oral cavity, resulting in solution or suspension. Allergic rhinitis is a high-prevalence chronic respiratory disease with a negative impact on the subject’s quality of life, work activities, productivity or school performance as well as on healthcare costs. Because of its benign nature, the importance of this condition is often underestimated. In the present study orodispersible tablet of antihistaminic agent was prepared by direct compression method using crosspovidone, Crosscarmellose and Indion 414, as superdisintegrants. FT-IR study shows that there is no significant interactions occur between drug and excipient. The tablets prepared were evaluated for various parameters like various density parameters, thickness, hardness, friability, disintegration time, wetting time and In-vitro dissolution time. All the parameters were found to be within limits. The developed formulation of levocetirizine batch F8 (10% Indion 414) showed good palatability and dispersed within 30 seconds as compare to crosscarmellose sodium and crosspovidone. When the results were compared with that of convectional tablets was found to be better with respect to simple manufacturing and allergic rhinitis.
Keywords: Orodispersible tablet, antihistaminic agents, superdisintegrants, allergic rhinitis.